Shaking the family tree: identification of novel and biologically active alternatively spliced isoforms across the KLF family of transcription factors. Issue 2 (7th November 2012) - Camacho‐Vanegas, Olga; Till, Jacob; Miranda‐Lorenzo, Irene; Ozturk, Berrin; Camacho, Sandra Catalina; Martignetti, John A.
Abstract : Alternative splicing represents a unique post‐transcriptional mechanism that increases the complexity of the eukaryotic proteome‐generating protein isoforms whose functions can be novel, diverse, and/or even antagonistic when compared to its full‐length transcript. The KLF family of genes consists of ≥17 members, which are involved in the regulation of numerous critical cellular processes, including differentiation, cell proliferation, growth‐related signal transduction, angiogenesis, and apoptosis. Using a strategy based on RT‐PCR, selective cloning, and promoter‐based assays of cancer‐relevant genes, we identify and characterize the existence of multiple biologically active KLF splice forms across the entire family of proteins. We demonstrate biological function for a number of these isoforms. Furthermore, we highlight a possible functional interaction between full‐length KLF4 and one of its splice variants in up‐regulating cellular proliferation. Taken together, this report identifies for the first time a more complete view of the genomic and proteomic breadth and complexity of the KLF transcription factor family, revealing the existence of highly expressed and biologically active isoforms previously uncharacterized. In essence, knowing that these KLF isoforms exist provides the first step toward understanding the roles of these genes in human health and disease.—Camacho‐Vanegas, O., Till, J., Miranda‐Lorenzo, I., Ozturk, B., Camacho, S. C., Martignetti, J. A. Shaking the family tree: identification of novel and biologically active alternatively spliced isoforms across the KLF family of transcription factors. FASEB J. 27, 432–436 (2013). www.fasebj.org